2007
DOI: 10.1016/j.cell.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Is a Negative Regulator of IL-1β Secretion as Revealed by Genetic and Pharmacological Inhibition of IKKβ

Abstract: IKKbeta-dependent NF-kappaB activation plays a key role in innate immunity and inflammation, and inhibition of IKKbeta has been considered as a likely anti-inflammatory therapy. Surprisingly, however, mice with a targeted IKKbeta deletion in myeloid cells are more susceptible to endotoxin-induced shock than control mice. Increased endotoxin susceptibility is associated with elevated plasma IL-1beta as a result of increased pro-IL-1beta processing, which was also seen upon bacterial infection. In macrophages en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
542
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 573 publications
(591 citation statements)
references
References 56 publications
43
542
5
1
Order By: Relevance
“…These observations, similar to those obtained with NLRP3 (7), reveal that it would be simplistic to deduce the physiologic role of NLRP12 only from in vitro assays, especially because it is well established that NF-B and IL-1␤ are part of interconnected networks (9,10), and that NF-B acts both on the induction and on the resolution of inflammation (10,11). Notably, the mechanisms underlying NLRP12-associated disorders may also vary according to the nature of the disease-causing mutation.…”
Section: Discussionsupporting
confidence: 68%
“…These observations, similar to those obtained with NLRP3 (7), reveal that it would be simplistic to deduce the physiologic role of NLRP12 only from in vitro assays, especially because it is well established that NF-B and IL-1␤ are part of interconnected networks (9,10), and that NF-B acts both on the induction and on the resolution of inflammation (10,11). Notably, the mechanisms underlying NLRP12-associated disorders may also vary according to the nature of the disease-causing mutation.…”
Section: Discussionsupporting
confidence: 68%
“…LPS is a known p65‐NF‐kB activator necessary for NLRP3 expression, but often a second stimulus such as ATP is required to activate inflammasomes (Greten et al ., 2007; Bauernfeind et al ., 2009). To evaluate p65‐NF‐kB activation, cell fractionation was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, these mice exhibited decline in tumor load, most of tumors presented in these mice were smaller in size compared to tumors in WT mice (72), which indicates that the inflammation-related release of cytokines might target epithelium thus promoting the expansion of transformed cells in an NF-B dependent manner, the expression of most of cytokines and growth factors characterizing the inflammatory process and involved in tumor progression relies on NF-B activation in immune cells (84). Taken …”
Section: The Role Of Nf-b In Promoting Carcinogenesis Of Colorectalmentioning
confidence: 94%
“…Activation of NF-B in epithelial cells is directly involved in the promotion and progression steps of colitis associated colorectal cancer. To investigate the role of NF-B in CRC development, conditional knockout mice lacking of the expression of IKKβ in the epithelial cells in AOM/DSS colitis associated CRC model was used by Greten et al (72), who demonstrated that the number of colon tumors reduced (but not tumor size), although inflammation was not reduced comparing wild type with knockout mice. They also showed that the decrease in tumor incidence was accompanied by increased epithelial apoptosis.…”
Section: The Role Of Nf-b In Promoting Carcinogenesis Of Colorectalmentioning
confidence: 99%